Patient-Reported Outcome Measures in Colorectal Surgery: Construction of Core Measures Using Open-Source Research Method. (October 2021) - El-Hussuna, Alaa; Rubio-Perez, Ines; Millan, Monica; Pellino, Gianluca; Negoi, Ionut; Gallo, Gaetano; Shalaby, Mostafa; Celentano, Valerio; Green, Ryan; Minaya-Bravo, Ana; Emile, Sameh; Smart, Neil J.; et al.
Purpose . The primary aim of the study was to review the existing literature about patient-reported outcome measures (PROMs) in colorectal cancer and IBD. The secondary aim was to present a road map to develop a core outcome set via opinion gathering using social media. Method . This study is the first step of a three-step project aimed at constructing simple, applicable PROMs in colorectal surgery. This article was written in a collaborative manner with authors invited both through Twitter via the #OpenSourceResearch hashtag. The 5 most used PROMs were presented and discussed as slides/images on Twitter. Inputs from a wide spectrum of participants including researchers, surgeons, physicians, nurses, patients, and patients' organizations were collected and analyzed. The final draft was emailed to all contributors and 6 patients' representatives for proofreading and approval. Results . Five PROM sets were identified and discussed: EORTC QLQ-CR29, IBDQ short health questionnaire, EORTC QLQ-C30, ED-Q5-5L, and Short Form-36. There were 315 tweets posted by 50 tweeters with 1458 retweets. Awareness about PROMs was generally limited. The general psycho-physical well-being score (GPP) was suggested and discussed, and then a survey was conducted in which more than 2/3 of voters agreed that GPP covers the most important aspects in PROMs. Conclusion . Despite the limitations of this exploratory study, it offered a new method to conduct clinical research with opportunity to engage patients. The general psycho-physical well-being score suggested as simple, applicable PROMs to be eventually combined procedure-specific, disease-specific, or symptom-specific PROMs if needed.